Reducing the Duration of Untreated Psychosis (DUP) in a US Community: A Quasi-Experimental Trial. Issue 1 (4th January 2022) - Srihari, Vinod H; Ferrara, Maria; Li, Fangyong; Kline, Emily; Gülöksüz, Sinan; Pollard, Jessica M; Cahill, John D; Mathis, Walter S; Yoviene Sykes, Laura; Walsh, Barbara C; McDermott, Glen; Seidman, Larry J; et al.
Abstract: Objective: Duration of Untreated Psychosis (DUP) remains unacceptably long and limits effectiveness of care. To determine whether an early detection campaign ("Mindmap") can reduce DUP in a US community setting. Methods: In this nonrandomized controlled trial, Mindmap targeted the catchment of one specialty first-episode service or FES (STEP, Greater New Haven) from 2015 to 2019, while usual detection efforts continued at a control FES (PREP, Greater Boston). Mindmap targeted diverse sources of delay through mass & social media messaging, professional outreach & detailing, and rapid enrollment of referrals. Both FES recruited 16–35 years old with psychosis onset ≤3 years. Outcome measures included DUP-Total (onset of psychosis to FES enrollment), DUP-Demand (onset of psychosis to first antipsychotic medication), and DUP-Supply (first antipsychotic medication to FES enrollment). Results: 171 subjects were recruited at STEP and 75 at PREP. Mindmap was associated with an increase in the number of referrals and in efficiency of engagement at STEP. Pre-campaign DUP (2014–2015) was equivalent, while Mindmap was associated with DUP reductions at STEP but not PREP. DUP-Total fell significantly in both the first and the second quartile (11.5 and 58.5 days reduction per campaign year, respectively). DUP-Demand and DUP-Supply fell in the third quartiles only (46.3 and 70.3 days reduction per campaign year, respectively). No reductions were detectable across all quartiles at PREP, but between site comparisons were not significant. Conclusions: This is the first controlled demonstration of community DUP reduction in the US, and can inform future early detection efforts across diverse settings.